Effect of Reinforcement Type Variation on Mechanical Properties of Epoxy Composite - Zen, Ahmad Norca Kurnia; Jumiadi; Widiastuti, Ike (TRANSMISI, 2025)
This research aims to examine the mechanical characteristics of polymer matrix composites reinforced with filler from various types of wood powder. The types of wood used are mahogany, sengon, and Dutch teak. The composites were fabricated using the hand lay-up method with a composition of 90% resin and 10% wood powder. A specimen without the addition of wood powder was also prepared for comparison. In this research, the mechanical properties tested were bending strength and impact resistance (ASTM D5687 standards). The bending test was performed using the 3-point bending method with a Universal Test Machine, while the impact test was conducted using the Charpy Test method. The bending test results indicated that the composite reinforced with mahogany achieved the highest bending stress value of 136.02 N/mm², an increase of 20% compared to the composite without wood powder reinforcement. The impact test results showed no significant changes in impact resistance values, with an F-value of less than 5% in the ANOVA analysis.